Winning the numbers, losing the war The other MDG report. - Social Watch Philippines ([Quezon City] Social Watch Philippines, 2010)
This report ‘Winning the Numbers, Losing the War: The Other MDG Report 2010’ produced by Social Watch Philippines is the other report on our country’s progress on the Millennium Development Goals (MDGs) and the prospects of achieving them by 2015.

The different articles in this alternative report, each in their own way, try to tease out the claimed achievements, dig into the underlying causes of failure to make the sort of progress expected of a middle income country,
and suggest ways of catching up and moving beyond the MDGs.

The blueprint and strategies need to be re-examined. We have to understand better why until now we continue to fail to reverse the poverty trend, to reduce high inequality, deep-seated corruption, high population growth, and mounting indebtedness. We need to learn how to deal squarely with the structural causes hindering our efforts towards social justice and sustainable development.

Keeping the minimalist MDG promises by 2015, or sooner, is an essential step before we could even begin to aspire for higher standards of well-being for all Filipinos.
- Foreword
- An urgent MDG message: Inadequate funding places MDGs at risk
- MDG chances: stability and vulnerability
- Losing the war on poverty: The Other MDG10 Report
- On poverty, hunger and employment: Off-track but not without hope
- Crossroads: Marginalization versus achieving universal primary education by 2015
- Filipino women in the lead-up to the 2015 MDG deadline
- From 2010 and beyond: children should live past age 5
- Improve maternal health: a move towards universalizing health care
- The rising challenge of HIV/AIDS and other diseases
- Not much time, but not without options: A review of the Philippines’ progress on achieving the MDG on environment sustainability
- Trade, debt and aid: MDG retardants
-The Bangsamoro Outlook on the Millennium Development Goals
- Updated Official List of MDG Indicators
Includes bibliographical references
Keywords: Quality of life -- Philippines; Poverty -- Prevention -- Philippines; Social indicators; Economic indicators